A Recent Overview of 1, 2, 3-Triazole-Containing Hybrids as Novel Antifungal Agents: Focusing on Synthesis, Mechanism of Action, and Structure-Activity Relationship (SAR). (6th January 2022) - Marzi, Mahrokh; Farjam, Mojtaba; Kazeminejad, Zahra; Shiroudi, Abolfazl; Kouhpayeh, Amin; Zarenezhad, Elham
Abstract : A pharmacophore system has been found as 1, 2, 3-triazole, a five-membered heterocycle ring with nitrogen heteroatoms. These heterocyclic compounds can be produced using azide-alkyne cycloaddition processes catalyzed by ruthenium or copper. The bioactive compounds demonstrated antitubercular, antibacterial, anti-inflammatory, anticancer, antioxidant, antiviral, and antidiabetic properties. This heterocycle molecule, in particular, with one or more 1, 2, 3-triazole cores has been found to have the most powerful antifungal effects. The goal of this review is to highlight recent developments in the synthesis and structure-activity relationship (SAR) investigation of this prospective fungicidal chemical. Also there have been explained drugs and mechanism of action of a triazole compound with antifungal activity. This review will be useful in a variety of fields, including medicinal chemistry, organic chemistry, mycology, and pharmacology.